Media and water communication, culture and perception - Garde-Hansen, Joanne 1975- (I.B. Tauris, 2021)
As flooding, drought and water scarcity become more pronounced due to climate change, so the way in which these events are presented in the media assumes greater significance. In particular, the media plays an important role in shaping the public perception and understanding of water issues, and debates around extreme weather events more generally. Joanne Garde-Hansen’s book offers a sustained and comprehensive exploration of media representations of water. Drawing on a wide range of media – including newspapers, digital, photography, radio, television and video, as well as empirical research on media and memory – she examines how drought, flooding and water management have been portrayed in the media, both historically and in the contemporary world. The use of the media by water institutions to manage public perceptions and the use of digital media by the public to engage with water companies is also included. A particular feature of the book is an examination of water and gender in developed nations. One of the first books to look at media representations of water, this pioneering work provides valuable insights for both scholarly and professional water research.
Keywords: Wasser; Berichterstattung; Massenmedien; Droughts; Floods; Mass media / Social aspects; Natural disasters in mass media; Water in mass media; Water-supply; Water / Social aspects; Eau / Approvisionnement; Inondations